2014
DOI: 10.4314/wsa.v40i4.19
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic, chromium, copper, iron, manganese, lead, selenium and zinc in the tissues of the largemouth yellowfish, <i>Labeobarbus kimberleyensis</i> (Gilchrist and Thompson, 1913), from the Vaal Dam, South Africa, and associated consumption risks

Abstract: Arsenic, chromium, copper, iron, manganese, lead, selenium and zinc in the tissues of the largemouth yellowfish, Labeobarbus kimberleyensis (Gilchrist and Thompson, 1913)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
4
15
0
Order By: Relevance
“…The dominant elements within L. capensis muscle tissue were As, Cu, Fe, Mn, Se and Zn, which were present at higher concentrations than Cd, Co, Cr, Ni, Pb and V. High concentrations of Cu (1.59 µg/g dw), Fe (16.49 µg/g dw) and Zn (29.4 µg/g dw) in muscle are not surprising in this tissue and these findings corroborate previous studies (Wepener et al, 2011;Subotić et al, 2013;Gilbert and Avenant-Oldewage, 2014). Furthermore, in comparison to other elements within muscle tissue, previous studies have reported high As, Mn and Se concentrations.…”
Section: Fish Tissue Concentrationssupporting
confidence: 90%
See 4 more Smart Citations
“…The dominant elements within L. capensis muscle tissue were As, Cu, Fe, Mn, Se and Zn, which were present at higher concentrations than Cd, Co, Cr, Ni, Pb and V. High concentrations of Cu (1.59 µg/g dw), Fe (16.49 µg/g dw) and Zn (29.4 µg/g dw) in muscle are not surprising in this tissue and these findings corroborate previous studies (Wepener et al, 2011;Subotić et al, 2013;Gilbert and Avenant-Oldewage, 2014). Furthermore, in comparison to other elements within muscle tissue, previous studies have reported high As, Mn and Se concentrations.…”
Section: Fish Tissue Concentrationssupporting
confidence: 90%
“…In the present study, the liver had accumulated the highest concentrations of Cu, Fe, Se and Zn. Gilbert and Avenant-Oldewage (2014) found that the liver of Labeobarbus kimberleyensis (Gilchrist and Thompson, 1913) had accumulated the highest concentrations of Cu (11.68 µg/g dw), Fe (113.22 µg/g dw), Se (2.57 µg/g dw) and Zn (32.6 µg/g dw), whilst Crafford and Avenant-Oldewage (2011) found that livers of Clarias gariepinus Burchell, 1822 had accumulated higher Cu (40.22 µg/g dw), Fe (2041.79 µg/g dw) and Zn (76.61 µg/g dw) levels than other tissues. In comparison to the these studies, L. capensis liver tissue possessed higher concentrations of Cu, Fe, Se and Zn.…”
Section: Fish Tissue Concentrationsmentioning
confidence: 99%
See 3 more Smart Citations